Increasing Interest and Learning Outcomes in Physics on Static Electricity Through the Teaching at The Right Level Approach in High School Student - Maulady An Nurul Islami; Supriyadi Supriyadi (Universitas Negeri Semarang, 2026)
This study aims to determine the improvement of problem-solving abilities of class XII-2 on the main topic of Static Electricity at SMA Negeri 5 Semarang through the Teaching at the Right Level (TaRL) approach. This study is a classroom action research conducted in two cycles. The subject of the classroom action research used 1 class XII-2 with 36 students at SMA Negeri 5 Semarang. Learning with the Teaching at the Right Level (TaRL) approach that does not refer to class levels and facilitates various characteristics of students. This classroom action research was conducted in two cycles. TaRL emphasizes teachers to provide different treatments to students. Data on learning interests were collected through questionnaires and data on learning outcomes through written tests with both being analyzed quantitatively. Through this study, it was obtained that the increase in students' learning interests increased from 2.99 in the good category to 3.61 in the very good category. Student learning outcomes increased from 58% below the KKM in cycle I, to 84% above the KKM in cycle II. The implementation of the Teaching at The Right Level (TaRL) approach can increase students' interest and learning outcomes in static electricity material in class XII-2 of SMA Negeri 5 Semarang.